The ethical chatbot: A viable solution to socio-legal issues. (December 2022) - Ng, Jenny; Haller, Emma; Murray, Angus
Chatbots are becoming important today because of their various technical functions. They are commonly known for providing legal guidance on processes and general information. However, chatbots can also help solve issues of social disconnectedness. This article takes a wide view of the various types of chatbot that deal with socio-legal issues, with a focus on the use of chatbots by organisations that provide certain forms of legal services, such as community legal services. It highlights the chatbot's ability to create a social impact, while ensuring adherence to rules of legal ethics and principles of ethics in Artificial Intelligence.